Business plan : Retail network in Kazakhstan - Taran, Alexey (2022)
The main goal of the thesis is to provide a business plan for creating a new retail network in the Republic of Kazakhstan which will provide people with everything needed in everyday life by opening small convenience stores within walking distance from their homes. The theoretical part covers the business plan structure and explains the necessary analyses. The practical part applies already described studies in theoretical one such as PESTEL, Porter’s five forces, SWOT, etc. The financial part of the business plan shows the potential launch phase budget for opening fifteen stores in two cities in the country. It provides information about the financial development strategy of the company for the following five years.